2011
DOI: 10.1107/s0108270111006639
|View full text |Cite
|
Sign up to set email alerts
|

Novel ion pairs obtained from the reaction of titanium(IV) halides with simple arsane ligands

Abstract: The compounds tert-butylarsenium(III) tri-μ-chlorido-bis[trichloridotitanium(IV)], (C(4)H(12)As)[Ti(2)Cl(9)] or [(t)BuAsH(3)][Ti(2)(μ-Cl)(3)Cl(6)], (II), and bis[bromidotriphenylarsenium(V)] di-μ-bromido-μ-oxido-bis[tribromidotitanium(IV)], (C(18)H(15)AsBr)(2)[Ti(2)Br(8)O] or [Ph(3)AsBr](2)[Ti(2)(μ-O)(μ-Br)(2)Br(6)], (III), were obtained unexpectedly from the reaction of simple arsane ligands with Ti(IV) halides, with (II) lying on a mirror plane in the unit cell of the space group Pbcm. Both compounds contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…15 [ t BuAsH 3 ][Ti 2 (m-Cl) 3 Cl 6 ] and [Ph 3 AsBr] 2 [Ti 2 (m-O)(m-Br) 2 Br 6 ] were serendipitous products from the reaction of t BuAsH 2 with TiCl 4 and AsPh 3 with TiBr 4 respectively. 16 DFT calculations on the adducts [Cl 3 M-M 0 (PCl 3 ) 4 ] (M = Ti, Zr, Hf; M 0 = Co, Rh, Ir) and the derivatives [R 3 M-M 0 L 4 ] (R = Cl, NH 2 ; L = PCl 3 , PH 3 , CO) indicate that bond strengths in [R 3 M-M 0 L 4 ] depend strongly upon R and L. Steric interactions between Zr and Hf with equatorial PCl 3 groups cause long M-Co bonds in [Cl 3 M-Co(PCl 3 ) 4 ] (M = Zr, Hf). 17 Reaction of TiF 4 and guanidine hydrochloride in EtOH gives the new layered hybrid material [Hgua] 2 Á[Ti 5 O 5 F 12 ].…”
Section: Halides and Their Complexesmentioning
confidence: 99%
“…15 [ t BuAsH 3 ][Ti 2 (m-Cl) 3 Cl 6 ] and [Ph 3 AsBr] 2 [Ti 2 (m-O)(m-Br) 2 Br 6 ] were serendipitous products from the reaction of t BuAsH 2 with TiCl 4 and AsPh 3 with TiBr 4 respectively. 16 DFT calculations on the adducts [Cl 3 M-M 0 (PCl 3 ) 4 ] (M = Ti, Zr, Hf; M 0 = Co, Rh, Ir) and the derivatives [R 3 M-M 0 L 4 ] (R = Cl, NH 2 ; L = PCl 3 , PH 3 , CO) indicate that bond strengths in [R 3 M-M 0 L 4 ] depend strongly upon R and L. Steric interactions between Zr and Hf with equatorial PCl 3 groups cause long M-Co bonds in [Cl 3 M-Co(PCl 3 ) 4 ] (M = Zr, Hf). 17 Reaction of TiF 4 and guanidine hydrochloride in EtOH gives the new layered hybrid material [Hgua] 2 Á[Ti 5 O 5 F 12 ].…”
Section: Halides and Their Complexesmentioning
confidence: 99%
“…As part of recent work into the synthesis of molecular precursors for the deposition of transition metal pnictide thin films (Potts et al, 2009;Thomas, Blackman et al, 2010;Thomas et al, 2011), we recently reported an unusual ligand-exchange reaction between TiCl 4 and As(NMe 2 ) 3 (Thomas, Pugh et al, 2010). The reaction of one equivalent of As(NMe 2 ) 3 with TiCl 4 did not afford the 1:1 adduct [TiCl 4 {As(NMe 2 ) 3 }].…”
Section: Commentmentioning
confidence: 99%
“…Preparations and properties of different mono‐ and polynuclear compounds have been reported 25. In general, these compounds are prepared by dissolving a metal tetrahalide in an organic solvent5,6 or ionic liquid4 in the presence of an organic cation. Compounds with [ M 2 X 9 ] – ‐ or [ M 2 X 10 ] 2– anions ( M = Ti, Zr, or Hf, and X = Cl, Br, or I) are reported in the literature 712…”
Section: Introductionmentioning
confidence: 99%